Paleoenvironmental implications and drainage adjustment in the middle reaches of the Sabarmati river, Gujarat: Implications towards hydrological variability. (1st October 2017) - Thokchom, Sarda; Bhattacharya, Falguni; Durga Prasad, A.; Dogra, N.N.; Rastogi, B.K.
Abstract: The dryland fluvial sequences exposed in the lower part of the Gujarat alluvial plain are investigated for palaeohydrological/palaeoclimatic reconstruction using conventional sedimentology, grain size analyses supported by optical chronology. Considering that the study area is cradling large-scale constructional activities, an attempt has also been made to assess the geotechnical properties of the sediments. It has been observed that the lower reaches of the Sabarmati valley have preserved record of fluvial aggradation since MIS-5 (90 ka) to MIS-3 (47 ka) whereas the onset of aeolian processes began at around 12 ka. Based on the sediment texture, the alluvial sequences are divided into the lower and upper units. The lower fluvial sequence is dated to 90–63 ka whereas the upper fluvial sequence is dated to 47 ka. The stratigraphic marker red soil is dated to 63 ka. The study indicates that the terrain experienced tectonic perturbations after ∼12 ka which was responsible for the shifting of the Sabarmati river from regional NE-SW to N-S which is more pronounced towards the upstream of the Sabarmati river basin while the landscape stability is observed towards the downstream consisting of the older alluvium dated to 90 ka. Geotechnical investigation reveals potentially liquefiable sand, which however have been compacted due to large scale calcretisation since their deposition.